Analisis Penerapan Teknik Bursa Paragraf dalam Menulis Karangan Siswa (Studi Kasus di SD Negeri 4 Cipedes) - Dadang (Universitas Muhammadiyah Bangka Belitung, 2020)
The purpose of this technique is that the students can analyze a paragraph in terms of the logic and coherent than a paragraph. By the way students take as many paragraphs cutout according to the time after that, they analyze it. This paragraph analyzes carried out on an essay to find out where the fault lies in the use of language essay students, especially the use of Sundanese and Indonesian are less precise. This study aims to determine the application and understanding of teachers on learning techniques used in writing essays. This study menggunakna qualitative research. This study is used to understand the events, incidents, the perpetrator in certain situations that are scientific and natural. Descriptive qualitative research always means a descriptive data analyzed phenomenon, not the form of numbers. Data collected in the form of words that includes writing notes, reports, and photos. The results showed the application of paragraphs exchange techniques in SDN 4 Cipedes applied in other ways, namely by way of example and make their own arrangements and then if there is an error in the use of language essay, teacher or cross fix errors that occur. Understanding of teachers in paragraphs exchange techniques affect student learning outcomes, especially writing essays. Students' skills in writing this essay will be increased by way of implementation and understanding of teachers to a learning technique in accordance with the steps that should be. Teachers also have been trying to apply these techniques, in different ways. The suggestion is teachers should apply and to better understand the steps paragraphs exchange technique to exactly fit the appropriate steps, because then the ability to write essay students will be maximized again.